Therapeutic targeting with DABIL‐4 depletes myeloid suppressor cells in 4T1 triple‐negative breast cancer model. Issue 5 (24th March 2021) - Parveen, Sadiya; Siddharth, Sumit; Cheung, Laurene S.; Kumar, Alok; Shen, Jessica; Murphy, John R.; Sharma, Dipali; Bishai, William R.
Abstract : In many solid tumors including triple‐negative breast cancer (TNBC), upregulation of the interleukin‐4 receptor (IL‐4R) has been shown to promote cancer cell proliferation, apoptotic resistance, metastatic potential, and a Th2 response in the tumor microenvironment (TME). Since immunosuppressive cells in the TME and spleen including myeloid‐derived suppressor cells (MDSCs) and tumor‐associated macrophages (TAMs) also express the IL‐4R, we hypothesized that selective depletion of IL‐4R‐bearing cells in TNBC would result in the direct killing of tumor cells and the depletion of immunosuppressive cells and lead to an enhanced antitumor response. To selectively target IL‐4R + cells, we employed DABIL‐4, a fusion protein toxin consisting of the catalytic and translocation domains of diphtheria toxin fused to murine IL‐4. As anticipated, DABIL‐4 has potent cytotoxic activity against TNBC cells both in vitro and in vivo . We demonstrate in the murine 4T1 TNBC model that DABIL‐4 significantly reduces tumor growth, splenomegaly, and lung metastases. Importantly, we also show that the administration of DABIL‐4 results in the selective depletion of MDSCs, TAMs, and regulatory T cells in treated mice, with a concomitant increase in IFN‐γ + CD8 effector T cells in the TME. Since the 4T1 antitumor activity of DABIL‐4 was largely diminished in IL‐4R knockout mice, we postulate that DABIL‐4 functions primarily as an immunotherapeutic by the depletion of MDSCs, TAMs, and regulatory T cells. NanoString analysis of control and treated tumors confirmed and extended these observations by showing a marked decline of mRNA transcripts that are associated with tumorigenesis and metastasis. In conclusion, we demonstrate that DABIL‐4 targeting of both tumor and immunosuppressive host cells likely represents a novel and effective treatment strategy for 4T1 TNBC and warrants further study. Abstract : Treatment with the interleukin‐4 diphtheria fusion toxin protein (DABIL‐4) targeted and killed both tumor cells and the immunosuppressive cell populations of the tumor microenvironment. DABIL‐4 treatment in a murine triple‐negative breast cancer (TNBC) model reduced MDSCs, tumor‐associated macrophages, and Treg cell populations and inhibited both tumor growth and metastasis. DABIL‐4 targeting likely represents a novel and effective treatment strategy for TNBC.